(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article analyzes the important role of parents in raising and educating a child, recognizing the family as the main and most influential social and educational environment in a child’s life. It highlights how parents’ attitudes, values, behavioral patterns, and activity in the upbringing process affect children’s moral development, academic achievement, emotional well-being, and social adaptation. It also emphasizes the importance of parents’ pedagogical and psychological competence, which helps them understand the developmental characteristics of their children, respond appropriately to their emotional needs, and support an effective educational process at home.